2018
DOI: 10.1159/000486403
|View full text |Cite
|
Sign up to set email alerts
|

What Effect Does Ethnicity Have on the Response to Ranibizumab in the Treatment of Wet Age-Related Macular Degeneration?

Abstract: Aims: To compare, in a single urban population, the visual outcomes of ranibizumab monotherapy in “White” (W) and “Non-White” (NW) patients with wet age-related macular degeneration (AMD). Procedures: Prospective data was collected from 434 eyes of 217 patients with wet AMD patients receiving intravitreal ranibizumab. Baseline and monthly LogMAR visual acuities were obtained. All patients received treatment under a “treat and extend policy” consisting of three monthly injections of ranibizumab, followed by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Our study found similar visual outcomes with a previous 1-year outcomes real-world study of predominantly Caucasian mCNV patients treated with ranibizumab (Hamilton et al 2020). Whether mCNV behave differently in Asian and Caucasian eyes, as neovascular age-related macular degeneration does (Mohamed, Gadhvi & Mensah 2018;Kokame et al 2019), is yet to be established. A post-hoc analysis of a subgroup of patients from the RADI-ANCE study [Ranibizumab And PDT (verteporfin) evaluation in mCNV] did not find any visual outcome difference between Caucasian and Asian patients (Holz et al 2016) Korol et al 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study found similar visual outcomes with a previous 1-year outcomes real-world study of predominantly Caucasian mCNV patients treated with ranibizumab (Hamilton et al 2020). Whether mCNV behave differently in Asian and Caucasian eyes, as neovascular age-related macular degeneration does (Mohamed, Gadhvi & Mensah 2018;Kokame et al 2019), is yet to be established. A post-hoc analysis of a subgroup of patients from the RADI-ANCE study [Ranibizumab And PDT (verteporfin) evaluation in mCNV] did not find any visual outcome difference between Caucasian and Asian patients (Holz et al 2016) Korol et al 2020).…”
Section: Discussionsupporting
confidence: 84%
“… 2020 ). Whether mCNV behave differently in Asian and Caucasian eyes, as neovascular age‐related macular degeneration does (Mohamed, Gadhvi & Mensah 2018 ; Kokame et al. 2019 ), is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stratifying our cohort to analyze ethnic differences in neovascular AMD generated unequal group sizes because of the greater prevalence of AMD in White populations. 67,68 Although these results reflect outcomes from a diverse set of patients from Moorfields Eye Hospital, it does not fully represent a global population. Considering the epidemiology of AMD as a multifactorial disease for which genetics, race, diet, and lifestyle play a role in disease development, additional studies using diverse datasets would be ideal to compare analyses.…”
Section: Study Limitationsmentioning
confidence: 84%